La cible Marx Dormoy (1936-1941) - Franck Tison (Criminocorpus)
During the night of july 25th 1941, Marx Dormoy was murdered in his bedroom at Relais de l’Empereur in Montelimar. Some Cagoulars were in command, who placed a bomb under his mattress. Their grudge was kept alive by the nationalist press as early as november 1936, when Marx Dormoy became Home secretary in the Front populaire-cabinet and stepped up the struggle against Jacques Doriot and the Cagoule. From then onwards, the former had to face regular shelling from the far-right press that meant to hold him up as a demon and a criminal. Cartoonists as well as journalists in that political trend thus found opportunities to vent their anticommunism, their anti-semitism as well as anti-republican stand. Their targets were Léon Blum, his cabinet and his ability to ensure law and order. They did their best to deride Montluçon’s mayor as a fictional character such as Fantômas or Dr Caligari in order to make him vulnerable. For 5 years, Marx Dormoy had to put up with the worst libel and slander as well as threats bu Doriot’s supporters and by the Cagoulars. Some of them took action in 1941.